KEDUDUKAN KAIDAH FIQHIYAH DALAM SISTEM EPISTIMOLOGI HUKUM ISLAM - Berliano Arrasyid; Zul Ikromi; Muhammad Hafis (Islamic Family Law, STAI Sangatta Kutai Timur, 2026)
This research is motivated by the tension between the limited nature of revealed texts and the dynamic reality of social change, which positions qawa’id fiqhiyyah (Islamic legal maxims) as a vital epistemological instrument to bridge partial rulings (furu’) with the universal objectives of Sharia (maqasid). The purpose of this study is to dissect the epistemological structure of Islamic law through the lens of legal maxims, analyze their authority within the Hanafi and Shafi'i traditions, and reconstruct their relevance using Jasser Auda’s systems approach. The research method employed is normative legal research based on a library study. Data were collected through documentation of primary and secondary literature, which were then processed using descriptive-analytical and hermeneutic techniques to deconstruct the Naqli-Aqli-Systemic reasoning. The results indicate that qawa’id fiqhiyyah represent an integration of bayani (textual), burhani (rational), and irfani (ethical-spiritual) epistemologies. There is a significant methodological distinction where the Shafi'i School employs a deductive approach, while the Hanafi School tends toward an inductive approach. Furthermore, through the features of Jasser Auda’s systems approach such as cognitive nature, openness, and multi-dimensionality legal maxims are transformed from mere products of past jurisprudence into a progressive and responsive ijtihad methodology facing global challenges. In conclusion, the reconstruction of legal maxims through a systems approach enables Islamic law to remain relevant as a mercy to all creation (rahmatan lil-alamin) by prioritizing human welfare and human rights as the primary orientations.